Social aspects - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Traditional crops often have cultural significance beyond their value as a source of food. In southern Africa, marula fruit are traditionally harvested by women, and there are special ceremonies during the harvesting season. In northern Ghana, yams have cultural and spiritual significance and are only grown by men. Four researchers discuss the social significance of traditional food plants in Africa and Central America.